Modifications of Legal Transactions - Rodna Živkovska; Tina Pržeska (Faculty of Law “Iustinianus Primus” at Ss. Cyril and Methodius University in Skopje, Republic of Macedonia, 2018)
Abstract: The paper examines the various types of modifications of legal transactions such as conditions, terms and special stipulations. Conditions as future and uncertain circumstances have various effects on the legal transaction depending on the type of condition (suspensive (precedent) or resolutive (consequent), positive or negative, causal, potestative or combined). The effect of the conditions also differ in different points in time such as the time before the fulfillment of the condition, the time after the fulfillment of the condition and the time when it becomes certain that the condition won’t be fulfilled. All such effects are presented and analyzed in the paper. Terms, unlike conditions, are certain and determined periods of time that suspend or terminate the legal transaction. The paper analyzes the legal effect of terms over legal transactions and to what extent the provisions of the Law of Obligations regulating conditions are applicable to terms. The question of computation of terms is also being analyzed as one of the important aspects of their fulfillment. Special stipulations as duties directed to one of the parties in a legal transaction are analyzed throughout the scope of the two general laws – the Law of Obligations and the Inheritance Law.
Peer-reviewed article
Keywords: legal transactions, contracts, civil law, conditions, terms, special stipulations, legacy